Системні проблеми розвитку газової промисловості України - Філіпковська, Лариса Олексіївна; Кривенко, Максим Ігоревич (НТУ "ХПІ", 2017)
Газова промисловість відіграє важливу роль в економічному розвитку України, в досягненні національної безпеки, в паливно-енергетичному комплексі та в народному господарстві в цілому. Проаналізовано енергобаланс України та стан підприємств газової промисловості, виявлено критичні моменти, які заважають розвитку газової галузі. Cформульовано комплекс проблем щодо забезпечення розвитку газової промисловості України з точки зору системного підходу до їх вирішення. Таким чином, обґрунтовано заходи для підвищення енергоефективності економіки держави.

The gas industry plays an important role in the economic development of Ukraine, in achieving national security, in the fuel and energy complex and in the national economy as a whole. Demand for natural gas is considered in the domestic, commercial and manufacturing sectors of the country's economy. Attention is drawn to state control in the gas industry. The energy balance of Ukraine and the state of the enterprises of the gas industry are analyzed. These enterprises are influenced by such factors as: technology, environmental impact, government policy, capital expenditure, investment and fuel prices. Critical moments that hamper the improvement of the gas industry have been identified. The complex of problems on ensuring of development of the gas industry of Ukraine from the point of view of the system approach to their decision is revealed and formulated. Thus, the measures to increase the energy efficiency of the state economy are just ified.
System problems of development of the gas industry of Ukraine
Keywords: первинні енергоресурси; паливно-енергетичний комплекс; енергетичний потенціал; енергоефективність; gas industry; primary energy resources; primary energy resources; fuel and energy complex; energy potential; energy efficiency